The Level of Vision Necessary for Competitive Performance in Rifle Shooting: Setting the Standards for Paralympic Shooting with Vision Impairment - Allen, Peter M.; Latham, Keziah; Mann, David L.; Ravensbergen, Rianne H. J. C.; Myint, Joy (Frontiers in Psychology, 2016)
The aim of this study was to investigate the level of vision impairment that would reduce performance in shooting; to guide development of entry criteria to visually impaired (VI) shooting. Nineteen international-level shooters without vision impairment took part in the study. Participants shot an air rifle, while standing, towards a regulation target placed at the end of a 10m shooting range. Cambridge simulation glasses were used to simulate six different levels of vision impairment. Visual acuity (VA) and contrast sensitivity (CS) were assessed along with shooting performance in each of seven conditions of simulated impairment and compared to that with habitual vision. Shooting performance was evaluated by calculating each individual’s average score in every level of simulated vision impairment and normalising this score by expressing it as a percentage of the baseline performance achieved with habitual vision. Receiver Operating Characteristic (ROC) curves were constructed to evaluate the ability of different VA and CS cut-off criteria to appropriately classify these athletes as achieving ‘expected’ or ‘below expected’ shooting results based on their performance with different levels of VA and CS. Shooting performance remained relatively unaffected by mild decreases in VA and CS, but quickly deteriorated with more moderate losses. The ability of visual function measurements to classify shooting performance was good, with 78% of performances appropriately classified using a cut-off of 0.53 logMAR and 74% appropriately classified using a cut-off of 0.83 logCS. The current inclusion criteria for VI shooting (1.0 logMAR) is conservative, maximising the chance of including only those with an impairment that does impact performance, but potentially excluding some who do have a genuine impairment in the sport. A lower level of impairment would include more athletes who do have a genuine impairment but would potentially include those who do not actually have an impairment that impacts performance in the sport. An impairment to contrast sensitivity could impact performance in the sport and might be considered in determining eligibility to take part in VI competition.